The evolution of endourology in the management of pediatric vesicoureteral reflux - Miyakita, Hideshi (Japanese Journal of Endourology and Robotics, 2023)
The prevalence of vesicoureteral reflux (VUR) has been estimated as 0.4 to 1.8％ among the pediatric population. In children with urinary tract infection the prevalence is typically from 30-50％ with higher incidence occurring in infancy. When correction of VUR is determined to be necessary, traditionally open ureteral reimplantation by a variety of techniques has been the mainstay of treatment. A detailed review of recent literature on the subject is performed find out various aspects of minimally invasive surgery in the treatment of VUR, highlighting evolution of management approaches in endourology.